The impact of Equity and Justice on the integration of the Islamic community (Islamic Sciences Journal, 2023)
The Holy Qur’an took great care of the moral system and social justice and spread the principle of equity and moderation among people, avoided injustice and oppression, and made this a part of the morals of our religion. The systems he called for, and he commanded us to implement them so that there is no excuse left for the Muslim to perpetuate corruption and corruption, enmity with others, and spread the spirit of hatred and malice that leads individuals and groups to commit injustices and foolishness that tear the nation apart.On this basis, and as a contribution from me to developing a sense of justice, equity, peaceful coexistence, not oppressing others, and respecting them as partners in the homeland, I chose to write on the topic: (The Impact of Equity and Justice in the Cohesion of the Islamic Society) as a title for research.The research plan required dividing it into an introduction and five chapters: The first topic is to define the vocabulary and terminology of the research title.In the second topic, I spoke about stewardship with justice, explaining the meaning of stewardship, linguistically and idiomatically, and clarifying that Allah commanded not to conceal testimony.In the third topic, I dealt with the application of justice from the fear of Allah - the Exalted, His Majesty.As for the fourth topic: I devoted it to talking about Allah love for the just.And in the fifth topic: I mentioned the command of Allah Almighty to be fair and pay the measure and the balance with equity.In conclusion: I mentioned the most important findings.
Keywords: effect, Installment, Justice, Application of justice, Quarantine in installments, Allah love for the just.